Characteristics of Electrodeposited ZnO Nanostructures: Size and Shape Dependence - F. E. Tazangi; A. Rahmati
Zinc oxide nanostructures were grown on Si (111) using a simple electrodeposition route. Crystalline structure, optical and morphological properties were studied using X-ray diffraction, reflectance and photoluminescence (PL) spectroscopy, and scanning electron microscopy (SEM), respectively. This work provides insight into the significance of deposition time on controlling the shape and size of ZnO structure and white emission. The thermally treated ZnO nanostructures show hexagonal wurtzite nanocrystalline structure (~10 nm). The quantum confinement effect and band filling have been discussed on optical band gap widening from 3.21 eV to 3.70 eV. The PL spectra have illustrated fundamental band-edge emission in UV region and defect emission in visible region
Keywords: Physics; Materials science